Atomistic simulations of shock-induced phase transformations in polycrystalline iron - Kadau, K; Germann, T; Lomdahl, P; Albers, R; Wark, J; Higginbotham, A; Holian, B (2007)
We report on large-scale non-equilibrium atomistic simulations of shock-induced transformations in poly crystalline iron samples. These simulations show that, depending on the crystallographic orientation of the body-centered-cubic (bcc) parent phase grains with respect to the shock direction, a significant fraction of the product phase can be face-centered-cubic (fcc) instead of the expected hexagonal-close-packed (hcp) structure. This observation is explained by the existence of different transformation mechanisms for shocks along different crystallographic directions. We conclude that the observation of different product phases can be explained by simple geometric considerations of the involved transformation mechanisms between the parent bcc structure and the product hcp and fcc structures. Ultrafast high-energy laser-based experiments are underway to further investigate this subject. © 2007 American Institute of Physics.